Solutions for the Speechless: New Directions in Post-Stroke Aphasia Treatment - Annibale, Alexandra (The Meducator, 2013)
An increasing number of Canadians will be affected by aphasia and other post-stroke communication disorders as the nation’s population continues to age. Recent studies have expressed concern in the face of this reality; the rehabilitative services being provided to post-stroke aphasia patients are often based on correlative evidence, and important quantitative benefits evoked from this form of therapy remain unclear. A new body of research is emerging, and is giving greater consideration to alternative forms of treatment for post-stroke aphasia—including novel therapy techniques and pharmacological interventions. Perhaps the findings of these studies will have an impact on the way Canada administers care to those suffering from this disorder.